Norm Exemption in States’ NPT Nuclear Disarmament Obligations - Masni, Melly (Global: Jurnal Politik Internasional, 2021)
The Nuclear Nonproliferation Treaty (NPT) is highly appreciated for its ability to stop further nuclear proliferation in the world. Since its existence, this treaty has been said to be successful in preventing potential states from possessing weapons of mass destruction. At least, there are more than 40 states who have the capability to develop their own nuclear programmes, although such programmes are restrained from coming to fruition. However, this successful story has not taken place in the area of nuclear disarmament. None of its nuclear weapon-owning members seem to proceed with realising a full disarmament aim. This raises the question of why the NPT is unable to achieve success in the field of nuclear disarmament as it has in the field of nuclear non-proliferation. The NPT does not only contain the idea of nuclear non-proliferation, but also the idea of nuclear disarmament. In understanding this question, using a political psychology approach, this study finds that nuclear-weapon states face the so-called moral dilemma between the desire to achieve national interests and the desire to fulfil social demands required by the international norm. By taking advantage of the shortcomings in the NPT narrative as well as relevant world situations, these states attempt to be exempted from dismantling nuclear weapons under their possession.